1995
DOI: 10.1093/chemse/20.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Ingestion by Pregnant Women Alters the Odor of Amniotic Fluid

Abstract: Amniotic fluid samples were obtained from 10 pregnant women undergoing routine amniocentesis procedure. Approximately 45 min prior to the procedure, five of the women ingested placebo capsules, whereas the remaining five ingested capsules containing the essential oil of garlic. Randomly selected pairs of samples, one from a woman who ingested garlic and the other from a woman who ingested placebo capsules, were then evaluated by a sensory panel of adults. The odor of the amniotic fluid obtained from four of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
117
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(125 citation statements)
references
References 11 publications
1
117
0
7
Order By: Relevance
“…Moreover, it has been shown that flavours from the mothers' diet are transmitted through amniotic fluid (39) and later though breast milk (40,41) . Therefore, flavours and components consumed in the mothers' diet are associated with, and may have a significant effect on, feeding preferences and practices in later life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that flavours from the mothers' diet are transmitted through amniotic fluid (39) and later though breast milk (40,41) . Therefore, flavours and components consumed in the mothers' diet are associated with, and may have a significant effect on, feeding preferences and practices in later life.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Moreover, the environment from which the newborn came, the amnion, contains compounds derived from flavors of foods eaten by the pregnant mother. 13,14 Such exposure to dietary transmitted flavors (eg, garlic, anise) in amniotic fluid has been shown to influence the newborn's facial, mouthing, and orienting responses to the flavor in the short-term. 15,16 Because some of these same flavors will later be experienced in breast milk, [17][18][19][20] the fetus and breastfed infant experience the flavors of their mother's diet before their first exposure to these flavors in solid foods.…”
mentioning
confidence: 99%
“…Evidence suggests that olfactory properties of breast milk overlap those of amniotic fluid, and that the positive or reinforcing qualities of amniotic fluid odor for newborns is soon superceded by those of breast milk (Varendi, Porter, & Winberg, 1997). The chemosensory properties of both amniotic fluid and breast milk depend on maternal diet (Mennella & Beauchamp, 1991;Mennella, Johnson, & Beauchamp, 1995). According to an emerging model of olfactory learning and feeding ecology among mammals, iterative exposure to odorants derived from maternal diet serve to influence dietary preferences of the infant, so that they in effect receive a dietary preference "education" via odorants in their primary, maternally derived, source of nutrition (Galef & Henderson, 1972;Mennella, Jagnow, & Beauchamp, 2001).…”
Section: Discussionmentioning
confidence: 99%